2022
DOI: 10.3389/fpsyg.2022.821891
|View full text |Cite
|
Sign up to set email alerts
|

The Pandemic and the “Perpetual Foreigner”: How Threats Posed by the COVID-19 Pandemic Relate to Stereotyping of Asian Americans

Abstract: We examined the “othering” of Asian Americans in the context of the COVID-19 pandemic. Given past evidence that pathogen-related threat perceptions can exacerbate intergroup biases, as well as salient public narratives blaming the Chinese for the pandemic, we assessed whether individuals experiencing a greater sense of threat during the pandemic were more likely to apply the “perpetual foreigner” stereotype to Asian Americans. Over a seven-week period, we recruited 1,323 White Americans to complete a measure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…These findings highlight the "perpetual foreigner" perspective of Asian Americans, a phenomenon in which Asian Americans are more closely linked with an Asian country of origin rather than the US. 37,38 Such findings echo previous studies that describe similar experiences by Asian American HCWs 5,6,8 and South Asians after 9/11. [39][40][41][42] Participants reported that these racialized experiences affected their mental health and made them feel invisible within school support structures, consistent with experiences described by other minoritized trainees in medicine 35,43,44 and Asian American HCWs.…”
Section: Discussionsupporting
confidence: 88%
“…These findings highlight the "perpetual foreigner" perspective of Asian Americans, a phenomenon in which Asian Americans are more closely linked with an Asian country of origin rather than the US. 37,38 Such findings echo previous studies that describe similar experiences by Asian American HCWs 5,6,8 and South Asians after 9/11. [39][40][41][42] Participants reported that these racialized experiences affected their mental health and made them feel invisible within school support structures, consistent with experiences described by other minoritized trainees in medicine 35,43,44 and Asian American HCWs.…”
Section: Discussionsupporting
confidence: 88%
“…During the COVID-19 pandemic, Asian people experienced an increase in microaggressions in the form of microassaults (Cheng et al, 2021 ; Wong-Padoongpatt et al, 2022b , c ) which mirrored the anti-Chinese and anti-foreigner sentiments firmly endorsed by the Trump administration (i.e., “China virus” and “Kung Flu”). Daley et al ( 2021 ) found that White People who blamed China for the COVID-19 pandemic were likely to rate Asian people as less American and more foreign. In a sample of Latinx and Asian college students, Huynh and colleague ( 2011 ) found those who endorsed the perpetual foreigner stereotype also showed identity conflict, lower sense of belonginess to America and consequently reported greater symptoms of depression, lower life satisfaction and hope.…”
Section: “Alien In One’s Own Land”: Racial Microaggressions For Latin...mentioning
confidence: 99%
“…Between June and August 2020, the first summer of the COVID‐19 pandemic in the US, we recruited 1996 participants from Amazon Mechanical Turk using the CloudResearch platform (Berinsky et al., 2012; Moss, 2018). Participants completed a battery of survey measures related to COVID‐19 and intergroup attitudes, a subset of which we report here (Daley et al, 2022, used other dependent variables from the same data collection). We aimed to have 25% of our sample from each census region (West, South, Midwest, Northeast), and 50% living outside of big cities (50% living in big cities).…”
Section: Methodsmentioning
confidence: 99%